Ionoacoustic tomography of the proton Bragg peak in combination with ultrasound and optoacoustic imaging - Kellnberger, Stephan; Assmann, Walter; Lehrack, Sebastian; Reinhardt, Sabine; Thirolf, Peter; Queiros, Daniel; Sergiadis, George; Dollinger, Guenther; Parodi, Katia; Ntziachristos, Vasilis (Scientific Reports, 2016)
Ions provide a more advantageous dose distribution than photons for external beam radiotherapy, due to their so-called inverse depth dose deposition and, in particular a characteristic dose maximum at their end-of-range (Bragg peak). The favorable physical interaction properties enable selective treatment of tumors while sparing surrounding healthy tissue, but optimal clinical use requires accurate monitoring of Bragg peak positioning inside tissue. We introduce ionoacoustic tomography based on detection of ion induced ultrasound waves as a technique to provide feedback on the ion beam profile. We demonstrate for 20 MeV protons that ion range imaging is possible with submillimeter accuracy and can be combined with clinical ultrasound and optoacoustic tomography of similar precision. Our results indicate a simple and direct possibility to correlate, in-vivo and in real-time, the conventional ultrasound echo of the tumor region with ionoacoustic tomography. Combined with optoacoustic tomography it offers a well suited pre-clinical imaging system.
CRIS-Team Scopus Importer:2023-03-08